Physico-chemical compositions of the red seedless watermelons (Citrullus Lanatus) - Yau, Ee Wen; Shamsudin, Rosnah; Muda, Noraziah; Chin, Nyuk Ling; Hassan, Osman (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Changes of physico-chemical properties such as size, weight, moisture content, total soluble solid (TSS), colour, pH, total acidity and sugar content of red seedless watermelon during storage at room temperature (± 28°C; 70-80% RH) were investigated. The average weight, diameter and length of red seedless watermelon were 5.94 kg, 22.0 cm and 21.8 cm respectively. The length to diameter ratio was 1.02. The statistical analysis indicated that total soluble solids of fruit decreased significantly (p<0.01), but no significant changes were found in pH and total acidity during ripening. Weight loss, moisture content and freezing point was found to be increased significantly (p<0.01) during ripening. Colour L* was found no significant changes but colour a* and b* increased significantly (p<0.1) throughout the ripening process. For sugar analysis, significant changes (p<0.1) in fructose and glucose were obtained, but no significant changes were observed in sucrose content during storage time. From the observation, the optimum eating quality of watermelon stored in room temperature (± 28°C; 70-80% RH) was within one week after harvest, although they can be stored up to 2 weeks. The data obtained is vital in order to apply in different field, purpose and application.